Hot workability and constitutive model of the Cu-Zr-Nd alloy. (December 2017) - Zhang, Yi; Sun, Huili; Volinsky, Alex A.; Tian, Baohong; Song, Kexing; Wang, Bingjie; Liu, Yong
Abstract: Hot deformation behavior of the Cu-Zr-Nd alloy was studied by using compressive tests in the temperature range of 550–900 °C and the strain rate range of 0.001–10 s −1 on the Gleeble-1500D thermo-mechanical simulator. The Cu-Zr-Nd alloy flow stress increased at higher strain rate and lower temperature. Based on the processing maps and microstructure, the optimal processing parameters for the Cu-Zr-Nd alloy are determined as 750-870 °C and 0.001–0.03 s −1 . The addition of Nd can promote the dynamic recrystallization. A new constitutive model, which compensates for the strain rate, is established according to the Arrhenius-type equation. The Zener-Hollomon parameter was also modified to compensate for the strain rate. The flow stress predicted by the constitutive equation is consistent with the experimental flow stress. Highlights: Hot deformation and dynamic recrystallization of the Cu-Zr-Nd alloy were studied. The optimal processing parameters for the Cu-Zr-Nd alloy were determined. The addition of Nd can improve the dynamic recrystallization of Cu- Zr alloy. Flow stress predicted by the constitutive equation is consistent with the experiment.